1993
DOI: 10.1161/01.cir.88.3.896
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic diagnosis of postinfarction regional pericarditis. Ancillary observations regarding the effect of reperfusion on the rapidity and amplitude of T wave inversion after acute myocardial infarction.

Abstract: First, premature reconcordancy of the ST segment and T wave after acute myocardial infarction is a sensitive, reasonably specific, and easily recognizable ECG manifestation of postinfarction regional pericarditis. Second, reperfusion is associated with accelerated evolution and deepening of the T waves following acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 11 publications
0
36
0
2
Order By: Relevance
“…1,3,4 While a rub is usually appreciated in systole, mid-diastole, and presystole, it is not always heard in all 3 phases and is transient in nature. 5,6 A total of 423 consecutive patients following myocardial infarction (MI) were evaluated for pericarditis using ECG and auscultation. Postinfarction pericarditis was diagnosed in 31 patients (7.3%) based on the presence of a pericardial rub, and of these 31 patients, only 1 had ECG changes suggestive of pericardial involvement.…”
Section: Infarct-associated Pericarditismentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,4 While a rub is usually appreciated in systole, mid-diastole, and presystole, it is not always heard in all 3 phases and is transient in nature. 5,6 A total of 423 consecutive patients following myocardial infarction (MI) were evaluated for pericarditis using ECG and auscultation. Postinfarction pericarditis was diagnosed in 31 patients (7.3%) based on the presence of a pericardial rub, and of these 31 patients, only 1 had ECG changes suggestive of pericardial involvement.…”
Section: Infarct-associated Pericarditismentioning
confidence: 99%
“…6,11,12 The diagnosis of regional pericarditis remains elusive, as it is uncommon and difficult to diagnose. 6,11 Following AMI, typical ECG changes suggestive of pericarditis are rare, and several studies have reported an extremely low incidence of ST-segment elevation and PR-segment depression in this setting. 1,3 While there are no ECG criteria to diagnose infarct-associated regional pericarditis, 6 2 atypical T-waves patterns of evolution have been described with a sensitivity and specificity of 100% and 77% respectively.…”
Section: Regional Pericarditismentioning
confidence: 99%
See 1 more Smart Citation
“…So far, regional pericarditis manifested as hemopericardium remained as a rare complication following large, transmural ventricular infarction [12]. Oliva and Mayo ever reported the atypical ECG natures with such regional pericarditis following MI, and so far there is no standardized ECG criteria in such clinical setting [3]. In their report of nearly 40 subjects, only 40% presented with persistent or recurrent ST segment elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Regional pericarditis as an uncommon situation after MI rarely causes large effusion or clinical tamponade and is extremely difficult to be distinguished from myocardial infarction per se by traditional ECG [3]. Several prior studies had reported an extremely low incidence of typical ST-segment elevation as a typical pattern of global pericarditis [4].…”
Section: Introductionmentioning
confidence: 99%